RE-THINKING FORFEITURE OF PATRIMONIAL BENEFITS WHEN A MARRIAGE DISSOLVES THROUGH DEATH - Siyabonga Sibisi (Obiter, 2022)
People marry for different reasons; some marry for love, companionship, the desire to procreate or social security; others just marry for money. The law should provide spouses that are innocent of any marital misconduct with financial protection at the end of the marriage. At the same time, the law ought to make sure that nobody benefits from a marriage that he or she has wrecked through marital misconduct at the expense of another. Section 9 of the Divorce Act 70 of 1979 seeks to achieve this by providing for forfeiture of patrimonial benefits. Over the years, our courts have clarified the application of this provision. However, some questions remain. Is it sufficient only to have regard to the duration of the marriage, the circumstances that gave rise to the breakdown of the marriage and substantial misconduct? Should our courts not look to other factors? Should section 9 not apply when a marriage ends through death under questionable circumstances? This article seeks to address these questions.